Chemical compositions, antioxidant, antimicrobial, and mosquito larvicidal activity of Ocimum americanum L. and Ocimum basilicum L. leaf essential oils - Ganesan Mahendran; Sornkanok Vimolmangkang (BMC, 2023)
Abstract Background Ocimum americanum L. (O. americanum) and Ocimum basilicum L. (O. basilicum) are highly valued aromatic medicinal plants. Their leaves are widely used as spices in traditional cuisine. Their essential oils (EOs) are extensively used in food, cosmetic, and pharmaceutical industries. This study aimed to investigate the main chemical profiles of O. americanum and O. basilicum leaf EOs and assess their effects on antibacterial, antioxidant, and larvicidal properties. Methods EOs were extracted from the leaves of O. basilicum and O. americanum using steam distillation in a Clevenger-type apparatus. The chemical constituents of the EOs were analyzed using gas chromatography-mass spectrometry. 2,2-Diphenyl-1-picrylhydrazyl (DPPH), ferric reducing antioxidant power (FRAP), and metal-chelating techniques were used to assess the free-radical scavenging capability of the oils. The extracted oils were also tested for their antibacterial activities via a disk-diffusion test and the broth microdilution method. Furthermore, the mosquito larvicidal (Aedes aegypti) activity was tested using standard protocols. Results Camphor (33.869%), limonene (7.215%), longifolene (6.727%), caryophyllene (5.500%), and isoledene (5.472%) were the major compounds in O. americanum leaf EO. The EO yield was 0.4%, and citral (19.557%), estragole (18.582%) camphor (9.224%) and caryophyllene (3.009%) were the major compounds found among the 37 chemical constituents identified in O. basilicum oil. O. basilicum exhibited a more potent antioxidant activity in DPPH, FRAP, and 2,2'-azino-bis(3-ethylbenzothiazoline-6-sulfonic acid tests than O. americanum. The zones of inhibition and minimum inhibitory concentration of the oils in the microdilution and disk diffusion methods were 8.00 ± 0.19 mm to 26.43 ± 2.19 mm and 3.12-100 µg/mL, respectively. At 400 ppm, O. basilicum and O. americanum EOs demonstrated larvicidal activity, with mortality ratios of 73.60% ± 0.89% and 78.00% ± 1.00%, respectively. Furthermore, after 30 min of exposure to O. americanum and O. basilicum EOs, the larval death rates were 73.60% ± 0.89% and 78.00% ± 1.00%, respectively. Conclusions The findings revealed that the EOs extracted from the leaves of O. basilicum and O. americanum exhibited reasonable antioxidant, antibacterial, and mosquito larvicidal potentials, and can be used as alternative medicine for the treatment of human health and larvicidal mosquito control.